Axial compression behavior of strength-gradient composite stub columns encased CFST with small diameter: Experimental and numerical investigation. (January 2023) - Ji, Jing; Li, Yun H.; Jiang, Liang Q.; Zhang, Yun F.; Liu, Ying C.; He, Ling J.; Zhang, Zhan B.; Wang, Yang
Abstract: In order to investigate axial compression behavior for strength-gradient composite stub columns encased concrete filled steel tube with small diameter (SGCC), the axial compression experiments of 13 SGCCs and 1 reinforced concrete (RC) stub column were carried out. The influence regularities of height-width ratio, confinement index ( θ ), stirrup ratio per unit volume ( ρ v ) and axial compressive strength of core concrete on the failure modes, load–displacement curves and load–strain curves of SGCCs were explored. The results showed that SGCCs mainly exhibited three failure modes under axial compression, including shear failure, central crushing and punching failure. By increasing θ and ρ v approximately, SGCCs could exhibit ductile failure instead of brittle failure. The deformations of steel tube, longitudinal steel bars, and concrete for SGCCs maintained coordinated during the loading process. Compared with ordinary RC column, the ultimate bearing capacity ( N u ) of SGCCs under axial compression was almost doubled. Based on the experimental results, 30 finite element (FE) models were designed to obtain the influence regularities of various parameters on N u of SGCCs. Applicability of existed design code to predict N u of SGCCs was also evaluated. Finally, a novel calculation formula for N u of SGCCs considering constraint effect of stirrups and steel tubes could be proposed, which were in good agreement with the experimental results.